2022
DOI: 10.1007/s00268-022-06637-3
|View full text |Cite
|
Sign up to set email alerts
|

Can the 5‐item Modified Frailty Index Predict Outcomes in Geriatric Trauma? A National Database Study

Abstract: Background Frailty results in increased vulnerability to adverse outcomes following trauma. We investigated the association between the 5-item modified frailty index (mFI-5) and outcomes in geriatric trauma patients. Methods The 2011-2016 Trauma Quality Improvement Program database was used to study outcomes in patients C 65 years old. The mFI-5 was measured and categorized into no frailty (mFI-5 = 0), moderate frailty (mFI-5 = 0.2), and severe frailty (mFI-5 C 0.4). Multivariable logistic regression analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
(35 reference statements)
0
9
1
Order By: Relevance
“…Although the mFI-5 has demonstrated prognostic value for post-injury outcomes, 2,3 in our study it lacked predictive value. Based on our findings, we concluded that commonly used frailty tools such as the mFI-5 are not accurate for predicting frailty-associated risks such as multiple fractures.…”
contrasting
confidence: 68%
See 1 more Smart Citation
“…Although the mFI-5 has demonstrated prognostic value for post-injury outcomes, 2,3 in our study it lacked predictive value. Based on our findings, we concluded that commonly used frailty tools such as the mFI-5 are not accurate for predicting frailty-associated risks such as multiple fractures.…”
contrasting
confidence: 68%
“…2 The mFI-5 has been demonstrated to provide excellent outcome data for geriatric trauma patients presenting with fractures. 2,3 However, the mFI-5 has not been used as a predictive metric to identify patients at higher risk for more severe injuries. 1 The aim of our study was to determine if the mFI-5 can be used to determine the relationship between increased frailty and multiple fractures following ground-level falls.…”
mentioning
confidence: 99%
“…We included results from 12 selected papers in the meta-analyses [ 20–31 ]. Nine studies of those were included for in-hospital mortality [ 20–23 , 25 , 26 , 29–31 ], three for LOS [ 24 , 25 , 28 ], nine for discharge to home [ 20–24 , 26 , 28 , 29 , 31 ] and eight studies for in-hospital complications [ 20–23 , 25 , 27 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The GRADE assessment for this result was a very low level of certainty. The level of certainty was downgraded because of a high risk of bias (four studies were at high risk of bias [ 20 , 26 , 29 , 31 ], four were moderate [ 21–23 , 30 ] and one was low [ 25 ]), potential publication bias and inconsistency (substantial heterogeneity, I 2 = 77). The inconsistency largely arose from the large Guiab et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation